The Effect of 7 MWp Selong On Grid Solar Power Plant (PLTS) on Electricity Network Stability in NTB - Farida Arinie Soelistianto; Farisan Robbani (Westscience Press, 2024)
The transition toward renewable energy is critical to achieving global sustainability goals, with solar power playing a significant role in diversifying energy sources. This study examines the effect of the 7 MWp Selong On-Grid Solar Power Plant (PLTS) on electricity network stability in West Nusa Tenggara (NTB), Indonesia. Using a qualitative approach, data were collected through in-depth interviews with five key informants, including policymakers, technical experts, and community representatives. Thematic analysis was conducted using NVivo software to identify the operational impacts, challenges, and opportunities of solar integration. Results indicate that the Selong PLTS contributes positively to voltage stability, reduces reliance on fossil fuels, and diversifies the energy mix. However, challenges such as intermittency, infrastructure limitations, and the absence of energy storage hinder its full potential. The study highlights the need for technological upgrades, stakeholder collaboration, and community engagement to optimize renewable energy adoption in NTB. These findings provide actionable insights for enhancing grid stability in regions integrating renewable energy.